Preference-conditioned multi-objective reinforcement learning for train carriage environment control - Boyuan Mu; Chunjun Chen; Lingwei Fei; Yutao Xia; Ji Deng (Building and Environment, 2026)

Novel insights into silver nanoparticles and silver ions promoting the transfer of antibiotic resistance genes through influencing phage transduction - Linzhi Li; Lingli Li; Qi Liao; Qi Wu; Chunjun Shen; Xinyu Zhang; Chunping Deng; Yongli He; Yujiao Zhang; Quanlin Long (Journal of Environmental Chemical Engineering, 2025)

Efficient control of antibiotic resistance in wastewater by UV/peracetic acid treatment: Unveiling distinct mechanisms behind the elimination of various contaminants - Lingli Li; Linzhi Li; Ming Yu; Xinyu Zhang; Chunjun Shen; Chunping Deng; Chuanshu He; Bing Yang; Lili Ma; Yucheng Liu; Bo Lai (Chemical Engineering Journal, 2024)

Correlation between the development of phage resistance and the original antibiotic resistance of host bacteria under the co-exposure of antibiotic and bacteriophage - Lingli Li; Mengya Zhou; Ming Yu; Xu Ren; Linzhi Li; Chunjun Shen; Chunping Deng; Yucheng Liu; Bing Yang (Environmental Research, 2024)

Internal pressure fluctuation modelling and passenger pressure comfort analysis of high-speed trains passing through extreme tunnels - Lu Yang; Chunjun Chen; Xiru Wang; Ji Deng; Qin Zheng (Building and Environment, 2024)

Catalpol Mitigates Alzheimer's Disease Progression by Promoting the Expression of Neural Stem Cell Exosomes Released miR-138-5p - Shengxi Meng; Huize Chen; Chunjun Deng; Zeyu Meng (Neurotoxicity Research, 2023)
Alzheimer’s disease (Alzheimer’s disease, AD) is a neurodegenerative disease characterized by senile plaque deposition and neurofibrillary tangles. The pathogenesis of AD is complicated and the drugs used to treat AD are single-targeted drugs, which can only improve or alleviate the symptoms of patients, but cannot delay or prevent the progress of the disease. Because of its ability to act on multiple targets, multiple systems, multiple links, and multiple pathways, Chinese herbal compound prescriptions have shown unique advantages in the research and treatment of AD. Our previous study has demonstrated the protect role of the Chinese medicine Rehmannia in AD. However, the underlying mechanism remains unclear. In the present study, both in vitro and vivo experiments were employed, and we found Catalpol (Ca), the main extract of Rehmannia, could mitigate AD progression both in vitro and in vivo by promoting miR-138-5p level in neural stem cell secreted exosomes